Folk Classification of Shea Butter Tree (Vitellaria paradoxa subsp. nilotica) Ethno-varieties in Uganda - Gwali, Samson; Okullo, John Bosco Lamoris; Eilu, Gerald; Nakabonge, Grace; Nyeko, Philip; Vuzi, Peter (Ethnobotany research and applications, 2011)
Folk knowledge has been the basis for selection and improvement of many food crops such as potatoes, sorghum, yams, cassava and rice. In Uganda, there is strong potential to utilize folk knowledge to select and domesticate the shea butter tree (Vitellaria paradoxa C.F. Gaertn.subsp. nilotica (Kotschy) A.N. Henry & Chithra & N.C. Nair), an important economic tree species. Farmers report high variation in fruit yield, tree form and pulp taste. In this study, we documented shea tree folk classification by interviewing 300 respondents, 15 focus groups and 41 key informants across three farming systems of Uganda. Data were analyzed using Kruskall-Wallis and Spearman’s tests, Chi-square, Multivariate, Factor and Discriminant Function Analyses. Folk classification and nomenclature of shea tree ethno-varieties is based on fruit/nut organoleptic (color and taste) and morphological attributes. Interestingly, despite the socio-cultural importance of shea oil, it does not feature as a factor in the folk classification and nomenclature of shea tree ethno-varieties. There was no significant difference in classification knowledge across the three farming systems (Kruskal – Wallis χ2 = 28, df = 28, p > 0.05; Spearman’s R > 0.8, p < 0.0001) although there was significant influence from ethnicity of the respondents (Pillai’s trace = 0.817, p < 0.001). While this study provides a record of shea tree ethno-varieties and associated classification criteria, there is need to validate these ‘ethno-varieties’ using detailed morphological, biochemical and molecular analyses.
Keywords: Vitellaria paradoxa, shea tree, ethno-variety, folk classification, organoleptic properties